2005
DOI: 10.1097/00124645-200511000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Role Transition for New Graduate RNs in a Semi-Rural Healthcare Setting

Abstract: This study describes and evaluates a structured program for orientation of new graduate registered nurses in a setting that has increased the number of new graduate RNs hired in recent years. It describes the elements of a supportive environment for new RNs and brings attention to the need to develop support and recognition of nurse preceptors, who are noted to be the cornerstone of support for new RNs as they make the transition from student to accomplished professional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…In addition to the one randomised control trial (Shepherd et al, 2007) and two quasi experimental studies (Newhouse et al, 2007;Komaratat and Oumtanee, 2009), a variety of research approaches were used including: one pre and post-test design (Young et al, 2008), one nonexperimental descriptive correlation study (Vasseur, 2009), one comparative intervention study as part of an action research project (Edmond, 2004), three descriptive comparative surveys (Beecroft et al, 2001;Halfer et al, 2008;Krugman et al, 2006), two cross-sectional descriptive studies (Crimlisk et al, 2002;Setter et al, 2011), eight longitudinal studies (Altier and Krsek, 2006;Beecroft et al, 2008;Beyea et al, 2010;Roud et al, 2005;Squires, 2002;Ulrich et al, 2010;Williams et al, 2007), one mixed methods (Beyea et al, 2007) and one 6 year evaluation study (Beecroft et al, 2006), one retrospective study (Friedman et al, 2011) and eight descriptive case studies (Allanson and Fulbrook, 2010;Goode et al, 2009;Kowalski and Cross, 2010;Leigh et al, 2005;Marcum and West, 2004;Messmer et al, 2004;O'Malley Floyd et al, 2005;Owens et al, 2001). In mixed method studies only the quantitative data have been extracted, the qualitative data are not reported in this review.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the one randomised control trial (Shepherd et al, 2007) and two quasi experimental studies (Newhouse et al, 2007;Komaratat and Oumtanee, 2009), a variety of research approaches were used including: one pre and post-test design (Young et al, 2008), one nonexperimental descriptive correlation study (Vasseur, 2009), one comparative intervention study as part of an action research project (Edmond, 2004), three descriptive comparative surveys (Beecroft et al, 2001;Halfer et al, 2008;Krugman et al, 2006), two cross-sectional descriptive studies (Crimlisk et al, 2002;Setter et al, 2011), eight longitudinal studies (Altier and Krsek, 2006;Beecroft et al, 2008;Beyea et al, 2010;Roud et al, 2005;Squires, 2002;Ulrich et al, 2010;Williams et al, 2007), one mixed methods (Beyea et al, 2007) and one 6 year evaluation study (Beecroft et al, 2006), one retrospective study (Friedman et al, 2011) and eight descriptive case studies (Allanson and Fulbrook, 2010;Goode et al, 2009;Kowalski and Cross, 2010;Leigh et al, 2005;Marcum and West, 2004;Messmer et al, 2004;O'Malley Floyd et al, 2005;Owens et al, 2001). In mixed method studies only the quantitative data have been extracted, the qualitative data are not reported in this review.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…These range from structured to more informal approaches. Structured approaches such as graduate programmes (Johnstone et al, 2008), residency programmes (Goode and Williams, 2004;Happell and Gough, 2007;Olson et al, 2001;Williams et al, 2007), orientation programmes (O'Malley Floyd et al, 2005;Young et al, 2008) and nurse internships (Beecroft et al, 2001, Ulrich et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Three further studies 28,30,31 reported 1 year retention as a percentage rate only, rates ranging from 77% to 94.5%. Marcum,29 reported that at 18 months post completion of the programme that 89% of orientees remained employed compared to 29% in 1999 and 41% in 2000 prior to the programme.…”
Section: Retentionmentioning
confidence: 99%
“…Knowledge was also measured objectively using a locally developed multiple choice questionnaire (MCQ). 28 sent out a questionnaire to 37 RNs, who had participated in a 4 month orientation programme within 2 acute hospitals in a semi-rural healthcare setting in Southern Oregon, USA. The response rate was 84% (31/37).…”
Section: Pre Test and Post Test Role Conception And Role Discrepancy mentioning
confidence: 99%
See 1 more Smart Citation